2019
DOI: 10.21203/rs.2.10717/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenotypic Analysis Combined with Tandem Mass Tags (TMT) Labeling Reveal the Heterogeneity of Strawberry Stolon Buds

Abstract: Background: Ramet propagation in strawberry (Fragaria × ananassa) is the most effective way in production. However, the lack of systematically phenotypic observations and high-throughput methods limits our ability to analyze the key factors regulating the heterogeneity in strawberry stolon buds. Results: From observation, we found that the axillary bud located in the first node quickly stepped into dormancy (DSB), after several bract and leaf buds were differentiated. The stolon apical meristem (SAM) degenerat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…In our previous research (14), the consumption of hydrogen-enriched drinking water was shown to reduce endometrial tumor volume, density and weight in a xenograft mice model (Figure S1), suggesting that drinking hydrogen-rich water (HRW) might be served as an effective treatment or adjuvant therapy for EC, while the mechanism of how they function remain unknow. To characterize the effect of hydrogen water on signal transduction, substrate specificity, and peptidase functional efficiencies, a new approach called quantitative multiplex substrate profiling by mass spectrometry (qMSP-MS) (15) which utilizes isobaric tandem mass tags (TMTs) was utilized herein. TMTs are available with different reactive groups, which enables deep proteome coverage for multiple samples in a reasonable amount of time (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research (14), the consumption of hydrogen-enriched drinking water was shown to reduce endometrial tumor volume, density and weight in a xenograft mice model (Figure S1), suggesting that drinking hydrogen-rich water (HRW) might be served as an effective treatment or adjuvant therapy for EC, while the mechanism of how they function remain unknow. To characterize the effect of hydrogen water on signal transduction, substrate specificity, and peptidase functional efficiencies, a new approach called quantitative multiplex substrate profiling by mass spectrometry (qMSP-MS) (15) which utilizes isobaric tandem mass tags (TMTs) was utilized herein. TMTs are available with different reactive groups, which enables deep proteome coverage for multiple samples in a reasonable amount of time (16,17).…”
Section: Introductionmentioning
confidence: 99%